DEVELOPMENT OF BAMBOO TWIGS BRIQUETTES AND HAZELNUT SHELL WASTE - Gusnia, Yessi
Energy is a very essential need for humans, but the reserves of non-renewable fossil fuels are dwindling, so a breakthrough is needed to produce alternative energy sources that are efficient, economic and environmentally friendly as a substitute for fossil fuels. Briquettes are an alternative energy source derived from biomass. In this study, the biomass used as raw material for making briquettes were bamboo twigs (RB) and hazelnut shell waste (CK). The briquettes were made using tapioca flour adhesive to study the mechanical properties of the briquettes, calorific value, ash content, and volatile matter. The dried RB and CK waste were processed into charcoal powder with a particle size of ~0,25 mm. Initially, a study was carried out to obtain the best briquette pressure value from the pressure test on the resulting briquettes. Then, the briquettes were made using pressure with that value, with various CK concentrations. The compressive test was carried out using a universal testing machine (UTM) and the calorific value test was carried out using bomb calorimeter IKA C 2000. The results showed that the value of ultimate strength, modulus of elasticity, strain pada saat fracture, and calorific value increases with increasing CK concentrations. Ash content and volatile matter decreases with increasing CK concentrations. In this study, the most optimum briquettes was CK-RB 8 which was made using 8/24 (w/w) of CK concentrations. The values of ultimate strength, modulus of elasticity, strain at fracture, calorific value, ash content, and volatile matter of the CK-RB 8 were 3.86 Mpa; 50 Mpa; 0.141; 6331 calorie/gram; 8%; 8.59%, respectively.